2017
DOI: 10.1126/science.aag1789
|View full text |Cite
|
Sign up to set email alerts
|

The [4Fe4S] cluster of human DNA primase functions as a redox switch using DNA charge transport

Abstract: DNA charge transport chemistry offers a means of long range, rapid redox signaling. Here we demonstrate that the [4Fe4S] cluster in human DNA primase can utilize this chemistry to coordinate the first steps of replication. Through DNA electrochemistry, we find that a change in oxidation state of the [4Fe4S] cluster acts as a switch for DNA binding. Single-atom mutations that inhibit this charge transfer, moreover, hinder primase initiation without affecting primase structure or polymerization. Generating a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
210
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(223 citation statements)
references
References 55 publications
12
210
0
Order By: Relevance
“…(1) contains the I271S mutation and exhibits an anomalous structure at the DNA:RNA-binding interface that is drastically different from the conserved structure of human p58C and its yeast ortholog determined by two independent groups in four different protein assemblies (25) (Fig. 1A).…”
Section: Main Textmentioning
confidence: 85%
See 2 more Smart Citations
“…(1) contains the I271S mutation and exhibits an anomalous structure at the DNA:RNA-binding interface that is drastically different from the conserved structure of human p58C and its yeast ortholog determined by two independent groups in four different protein assemblies (25) (Fig. 1A).…”
Section: Main Textmentioning
confidence: 85%
“…Without any explanation or qualification, O’Brien et al assumed that the β-hairpin structure in their mutated p58C binds the RNA:DNA substrate in the same way as the α-helical structure in wild-type (WT) p58C (see Figs. 3A, 3B, and S6 in (1)). Moreover, the authors concluded that Y345 and Y347, which are adjacent in the mutated p58C (Fig.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact role of the Fe-S clusters in DNA metabolism proteins has been long debated. Interestingly, recent studies suggest that the redox state of Fe-S repair enzymes is crucial for their ability to find and repair DNA lesions (93). Prior to the most recent exciting investigations, it was postulated that the main role of the Fe-S clusters in DNA metabolism enzymes was to provide structural stability (94).…”
Section: How Are Fe-s Clusters Delivered To Correct Recipient Proteins?mentioning
confidence: 99%
“…Moreover, a recent study revealed that DNA-mediated ET played an important role in primase functions. 5 To clarify chemical roles of ET in vivo, we need to study DNA-mediated ET under crowded conditions, because the intracellular environment is highly crowded with 2040 wt % various biomolecules. Crowding by biomolecules causes changes in structures and stabilities of DNA as well as enzymatic reactivities to DNA.…”
mentioning
confidence: 99%